‘Inner movement’ between practices of meditation, martial arts, and acting: a focused examination of aff ect, feeling, sensing, and sensory attunement1 - Zarrilli , Phillip B. (Pygmalion. Revista de teatro general y comparado, 2025)
‘Inner movement’ between practices of meditation, martial arts, and acting: a focused examination of aff ect, feeling, sensing, and sensory attunement1